Researching children's popular culture : the cultural spaces of childhood - Mitchell, Claudia (Media, education and culture., 2002)
The authors focus primarily on methods of researching children's popular culture as well as offering analysis of such phenomena as children's websites and the Internet, and popular toys like Barbie.